Improving Listening Skills Through the Use of Mondly and Busuu Apps Subject: Comparative Study Using the Mondly and Busuu Apps - Nila Sari Syafitri; Nabiela Fahma; Lailatul Hana Maftuhah; Taufik (Raja Zulkarnain Education Foundation, 2026)
This study aims to investigate the extent to which the Mondly and Busuu applications can enhance students' listening skills in learning Arabic. This study uses a quasi-experimental method with an unequal control group model. There were two groups, each consisting of 15 people, who studied using the applications for a certain period. The data collected through initial and final tests were then analyzed using several statistical tests, such as normality, homogeneity, paired t-tests, and independent t-tests. The results showed that both apps significantly improved listening skills, as evidenced by the large difference between the pre-test and post-test scores and a significance value of p < 0.001. However, the comparison test between the two groups revealed no significant difference in post-test scores using Mondly andBusuu (p = 0.327). These results indicate that both applications are equally effective in improving Arabic speaking comprehension. This study confirms that mobile learning can be a good supporting tool for flexible, interactive language learning that is tailored to the needs of learners.